The effect of public - private partnerships on ultra - poor households in Bangladesh: Evidence from the IGVGD programme - Khanom, Nilufa Akhter (2011)
The problems of poverty is particularly; severe in Bangladesh. To achieve the national development goals and especially to reduce poverty, the Government of Bangladesh his started to experiment with cooperative approaches involving the private sector and NGOs. Public-Private Partnership (PPP) have been introduced as one of these novel approaches to poverty alleviation in Bangladesh. Income Generation for Vulnerable Group Development (IGVGD) is one of the important PPP arrangements under the Social Safety Net Programmes (SSNP) in Bangladesh. This article explores the effects of the IGVGD programme from the survey of sixty-six IGVGD household from fifteen Unions of five Districts. The survey results show an insignificant improvement in income levels. However, the survey results reveal that IGVGD is effective for ensuring food security. The programme also demonstrates noteworthy attainments in improving the rates of school enrolments of children; and in health consciousness such as immunization of children, access to safe drinking water, and hygienic sanitation. - Reproduced.
Keywords: Public private partnerships - Bangladesh; Public private partnerships